2017
DOI: 10.1209/0295-5075/119/27002
|View full text |Cite
|
Sign up to set email alerts
|

Topological phase stability and transformation of bismuthene

Abstract: Two-dimensional topological materials, in the form of ultrathin films grown on substrates, are outstanding candidates for spintronic applications. Their electronic structures including the topological class can be tuned or altered by strain and isoelectronic substitutional alloying. First-principles calculations show that the topological order of a monolayer Bi, bismuthene, is unusually robust against strain and changes in spin-orbit coupling strength. The phase diagram shows a large area in which the system i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…Group-V elemental and alloy crystals have attracted significant attention since the first fabrication of blackphosphorous-based transistors [7] and the discovery that Bi 1−x Sb x is a three-dimensional (3D) topological insulator [47,48]. Because of the strong spin-orbit coupling in Bi, many of its known allotropes are topologically nontrivial: α-Bi [49,50], β-Bi [51], and even bulk Bi [52] have all been reported to possess nontrivial topology, and most recently exotic hinge states have been reported in Bi nanowires [53]. An area of active investigation is whether the topological properties survive in the low-dimensional forms of these materials [45,50].…”
Section: B Topological Group-v Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Group-V elemental and alloy crystals have attracted significant attention since the first fabrication of blackphosphorous-based transistors [7] and the discovery that Bi 1−x Sb x is a three-dimensional (3D) topological insulator [47,48]. Because of the strong spin-orbit coupling in Bi, many of its known allotropes are topologically nontrivial: α-Bi [49,50], β-Bi [51], and even bulk Bi [52] have all been reported to possess nontrivial topology, and most recently exotic hinge states have been reported in Bi nanowires [53]. An area of active investigation is whether the topological properties survive in the low-dimensional forms of these materials [45,50].…”
Section: B Topological Group-v Materialsmentioning
confidence: 99%
“…Because of the strong spin-orbit coupling in Bi, many of its known allotropes are topologically nontrivial: α-Bi [49,50], β-Bi [51], and even bulk Bi [52] have all been reported to possess nontrivial topology, and most recently exotic hinge states have been reported in Bi nanowires [53]. An area of active investigation is whether the topological properties survive in the low-dimensional forms of these materials [45,50]. In fact the 2D forms of these materials are interesting because of the crystalline symmetries that are adopted.…”
Section: B Topological Group-v Materialsmentioning
confidence: 99%
“…calculations predicted that the bandgap is changed and closed by the tensile strain. [12][13][14] In the previous experiment, Bi(111) thin-film formed on a Si(111) and Bi 2 Te 3 substrate shows the lattice constant a = 4.54 Å 4) and a = 4.38 Å 8) respectively. It is reported that topological electronic states of Bi(111) thin-films are changed by the epitaxial strain of these different substrate.…”
mentioning
confidence: 94%
“…32) However, the system always has Z 2 = 1; therefore, strained single bilayer Bi(111) preserves the Z 2 topological insulator phase. 13,14) Figure 2 We investigated the electric-field-induced Z 2 topological phase transition. Figure 3(a) shows a topological phase diagram of strained systems under electric fields.…”
mentioning
confidence: 99%
“…The electronic properties of single‐layer b‐bismuthene change by applying electric field and strain significantly . Unstrained single‐layer b‐bismuthene is a semiconductor while strained single‐layer b‐bismuthene is metal in strains more compress than −8% and has a transition point at strain = 5% . Following the exploration of group V monolayers' properties, it is attractive to investigate the electronic and optical behavior of single‐layer b‐bismuthene in its semiconducting regions.…”
Section: Introductionmentioning
confidence: 99%